Expression of bcl-2 protein in gastric carcinoma and its significance - Liu, Hai-Feng (World J Gastroenterol, 1998)
AIM: To further study the role of bcl-2 protein expression in gastric carcinogenesis and tumor progression. METHODS: Using immunohistochemical staining, the bcl-2 protein expression in 50 cases of gastric carcinoma and its relation to clinical status and pathomorphological parameters were observed. RESULTS: Forty-one (82%) cases were positive for bcl-2 protein staining which was located in the cytoplasm and nuclear membrane of tumor cells. The rate of bcl-2 protein expression was not correlated with the patient, sex, tumor size, lymph node status or clinical stages (P > 0.05). It was strongly associated with intestinal-type tumors and poorly differentiated tumors (P < 0.05 and P < 0.01). CONCLUSION: Aberrant bcl-2 protein expression appears to be specifically associated with development of intestinal-type gastric carcinoma, bcl-2 protein expression might play an important role in the early development/promotion and phenotypic differentiation of gastric carcinomas, but not in tumor progression.